Clinical characteristics and outcomes of children with rheumatic heart disease: a global rheumatic heart disease registry (REMEDY) sub-analysis - Makate, Sindiswa A (Department of Paediatrics and Child Health, 2022)
Background: Despite Rheumatic Heart Disease (RHD) contributing to an estimated disease burden in 2019 of 40 million people and 285 500 deaths, few studies document the characteristics and outcomes in children. We undertook a sub-analysis of children from the multi-centre prospective two-year global Rheumatic Heart Disease Registry (REMEDY) to document their presentation, clinical characteristics and outcomes. Methods: Nine-hundred and twenty-one children were enrolled into the REMEDY registry among the 3,343 symptomatic RHD patients from 25 hospitals in 12 African countries, India and Yemen and followed up over 24 months to assess characteristics, complications and outcome. Results: More than half of the children enrolled in the REMEDY study presented with severe valvular heart disease; 60% had more than one valve involved, 30% were classified as NYHA class III/IV and 17.7% died within 24 months. Just over 20% of children were not on penicillin prophylaxis. Although 20% met criteria for surgery, only less than 9% (n=78, 8.5%) had had percutaneous or surgical intervention with half from upper-middle-income countries. The major risk factors associated with mortality included older age (Hazard Ratio (HR): 1.01, p=0.001) and atrial fibrillation or flutter (HR: 2.3, p=0.028). Female gender(HR: 0.68, p=0.062) and education level above primary school (HR: 0.88, p=0.68) did not confer significant protection. However, a past medical history of ARF conferred some protection against mortality (HR: 0.61, p=0.031). In follow-up, 30% (n=238, 29.6%) of children experienced an adverse cardiovascular event, nearly 15% (n=114, 14.1%) were hospitalised and six young women became pregnant during the study period. Conclusion: Children with RHD in low- and middle-income countries are severely affected, with significant mortality and morbidity. The use of penicillin was suboptimal and the substantial need for surgery is evident. Our findings support the recommendations of the World Health Assembly (WHA) Resolution 71.14 passed in May 2018 for consistent provision of penicillin, integrated collaborative efforts focused on children and adolescent health as well as access to specialised services including cardiac surgery.